Summary of the research Use the learning-by-learning strategy with an educational device to teach and retain the front and back hitting skills of a tennis ball - Tahseen, Tahseen Hosni (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to use the learning strategy by mastering with an educational device to teach and retain the front and back hitting skills of the tennis ball, as well as to identify the effect of using the learning by mastery strategy with an educational device to teach and retain the skills of front and back hitting the tennis ball, since learning by mastery of educational strategies that depend on skill with Feedback taking into consideration note the individual differences of learners in the learning process, as the researcher used the experimental approach to its suitability to solve the research problem and the design of the two equivalents with the same Tbarren tribal random selection and post, as the research sample consisted of students from the Phase III Division (c) in the Faculty of Physical Education and Sports Science at the University of Baghdad and by (20) Students, and by lot they were randomly divided into two experimental and control groups, each group (10) students, as the numbers were randomly drawn (1-20), so the individual numbers represented the experimental group and even numbers represented the control group, as well as the use of appropriate means, tools and devices , And the exploratory experiment was conducted, as well as conducting tribal tests for the two groups, applying the educational curriculum, then applying the tests enabling the experimental group after four weeks, then conducting the post-tests for the two groups, and then the data was emptied and statistically processed, and then presented and analyzed Discussed, the researcher reached several conclusions, namely : 1. The learning-by-doing strategy greatly assisted in teaching and retaining the front and back hitting skills of tennis 2. The educational system has greatly contributed to the teaching and retention of the front and back hitting skills of tennis . 3. That the learning-by-learning strategy with an educational apparatus had a positive effect in teaching and retaining the skills of front and back strokes of the tennis ball . The researcher reached several recommendations : 1. Using the learning strategy by mastering the educational process to achieve the best possible learning . 2. Use a variety of educational equipment to teach basic tennis ball skills . 3. Use other modern educational strategies on other sports .